Magnetic resonance of the thoracic aortic disease - Berden, Pavel (Radiology and oncology (Ljubljana), 2000)
Conventional ECG gated spin-echo (SE) magnetic resonance imaging (MR) and magnetic resonance angiography (MRA) are excellent methods for diagnosing thoracic aortic disease. SE image provides a good spatial resolution for defining aortic anatomy and relationships to adjacent tissues. MRA shows flow but temporal resolution is inferior to conventional MR images. Contrast-enhanced 3D (three-dimensional) MRA is very accurate for defining thoracic aortic anatomy and is particularly good for defining branch vessel abnormality. The sensitivity and specificity for diagnosing aortic dissection are the highest in comparison to other modalities (echocardiography, CT angiography) and range from 95% to 100% and 94% to 100%, respectively. MR can define clearly the full diameter of aortic aneurysm and also shows the amount of thrombi within it and its craniocaudal extent. A combination of SE and cineMRA is usually necessary. The same sequence with contrast enhancement provides all the required information on the congenital abnormalities of the aorta. MR is very reliable in congenital aortic abnormalities, aortic aneurysmand aortic dissection in hemodynamically stable patients. It should beused for all chronic thoracic aortic disease and postsurgical follow-up. Unstable patients that need intensive hemodynamic monitoring are unsuitable for MR.
Keywords: Aneurysm, dissecting; aorta; Aorta, thoracic; Aortic aneurysm, thoracic; Aortic diseases; Aortic rupture; Contrast media; diagnostika; Echocardiography; Follow-up studies; kardiovaskularne bolezni; Magnetic resonance angiography; Magnetic resonance imaging; Sensitivity and specificity; slikanje z jedrsko magnetno resonanco; Thrombosis; Treatment outcome